2002
DOI: 10.1038/sj.onc.1205640
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction of protein kinase CK2 and c-Myc in lymphomagenesis

Abstract: Protein kinase CK2 (formerly casein kinase II) is frequently upregulated in human cancers, and transgenic expression of CK2a in lymphocytes is oncogenic. Lymphomagenesis is dramatically acclerated by coexpression of a c-myc transgene, suggestive of a synergistic interaction between the kinase and the transcription factor. Since c-myc can be phosphorylated by CK2, we hypothesized that the synergy between CK2 and c-myc might be due to a functional interaction of the two molecules. Pharmacologic inhibition of CK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(99 citation statements)
references
References 48 publications
2
97
0
Order By: Relevance
“…For example, in studies on TRAIL mediated induction of apoptosis, we observed downregulation of cFLIP L which was prevented by overexpression of CK2 in PC-3 prostate cancer cells (Wang et al, 2006a); the significance of this observation may relate to the recent documentation that cFLIP L expression is necessary and sufficient to maintain resistance to TRAIL-induced apoptosis in prostate cancer cells (Zhang et al, 2004). Upon phosphorylation by CK2, Max is rendered insensitive to cleavage by caspases (Krippner-Heidenreich et al, 2001) while Myc is stabilized by CK2 mediated phosphorylation (Channavajhala and Seldin, 2002). In the NF-κB pathway, downregulation of CK2 by employing antisense CK2α resulted in nuclear translocation of NF-κB p65 (Ahmad et al, 2006).…”
Section: Downstream Targets Of Ck2 In the Apoptotic Machinerymentioning
confidence: 49%
“…For example, in studies on TRAIL mediated induction of apoptosis, we observed downregulation of cFLIP L which was prevented by overexpression of CK2 in PC-3 prostate cancer cells (Wang et al, 2006a); the significance of this observation may relate to the recent documentation that cFLIP L expression is necessary and sufficient to maintain resistance to TRAIL-induced apoptosis in prostate cancer cells (Zhang et al, 2004). Upon phosphorylation by CK2, Max is rendered insensitive to cleavage by caspases (Krippner-Heidenreich et al, 2001) while Myc is stabilized by CK2 mediated phosphorylation (Channavajhala and Seldin, 2002). In the NF-κB pathway, downregulation of CK2 by employing antisense CK2α resulted in nuclear translocation of NF-κB p65 (Ahmad et al, 2006).…”
Section: Downstream Targets Of Ck2 In the Apoptotic Machinerymentioning
confidence: 49%
“…2D) and TBB (4,5,6,7-tetrabromo-2-azabenzimidazole; IC 50 : 0.9 mM) (Fig. 2E) [39,40]. The analyses revealed that the CK2 inhibitors Apigenin and TBB were able to efficiently suppress Thr 244 phosphorylation Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The analyses revealed that the CK2 inhibitors Apigenin and TBB were able to efficiently suppress Thr 244 phosphorylation Fig. 2D and E) [39,40]. Thus, CK2 appears to be the protein kinase that targets APRIL Thr 244 .…”
Section: Resultsmentioning
confidence: 94%
“…37 Parallel and subsequent work demonstrated in this model that CK2 cooperates both with loss of the tumor suppressor p53 and with overexpression of the oncogene c-myc in causing lymphocyte proliferation and clonal expansion. 38,39 These initial studies established a proliferative and apoptosis-protective role for CK2 in T lymphocyte in the mouse. However, a more straightforward role of this kinase in lymphocyte oncogenesis has been recently suggested by studies in human lymphoid tumors, both arising from precursor cells and from mature lymphocytes.…”
Section: Ck2 In Lymphoid Tumors Mouse Modelsmentioning
confidence: 99%